2003
DOI: 10.1002/syn.10209
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related loss of synapses in the frontal cortex of SAMP10 mouse: A model of cerebral degeneration

Abstract: SAMP10 mouse is a model of brain aging in which senescence is characterized by cerebral atrophy most prominent in the frontal cortex, deterioration in performance of learning and memory tasks, and alterations of the central dopaminergic system. The present study investigates age-related changes in the expression of synapse-related proteins to determine whether the number of synapses is decreased in SAMP10 mice. We quantified expression levels of synaptophysin, a presynaptic protein, and of PSD-95, a postsynapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 33 publications
3
32
0
Order By: Relevance
“…[39][40][41] In aged SAMP10, a decreased level of synaptophysin, a presynaptic vesicular protein, and synaptic loss have been observed in the atrophied anterior cerebral cortex, 21) and cognitive performance has been found to be associated with alterations in cerebral atrophy 24,42) and the level of synaptophysin. 23) In mice that ingested b-CRX, however, the wet weight of the cerebrum did not change significantly and an increase of synaptophysin was observed but it was not significant (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41] In aged SAMP10, a decreased level of synaptophysin, a presynaptic vesicular protein, and synaptic loss have been observed in the atrophied anterior cerebral cortex, 21) and cognitive performance has been found to be associated with alterations in cerebral atrophy 24,42) and the level of synaptophysin. 23) In mice that ingested b-CRX, however, the wet weight of the cerebrum did not change significantly and an increase of synaptophysin was observed but it was not significant (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…20,21) Moreover, the production of superoxide anion was higher in SAMP10 than in other mice with normal longevity and brain function. 22) In addition, our previous data indicates that the consumption of green tea catechin (catechin), a potent antioxidant in green tea, suppressed brain dysfunction and DNA oxidative damage in aged SAMP10.…”
mentioning
confidence: 94%
“…The SAMP8 tend to have more accelerated impairments of learning and memory, and the deficits are more pronounced than the SAMP10 (Miyamoto 1997). Furthermore, previous research has highlighted the age-related hippocampal changes in the SAMP8, whereas much of the focus of research in the SAMP10 has been on neocortical changes, although this distinction is not absolute (Flood and Morley 1998;Han et al 2004;Sano et al 2004;Shimada 1999;Shimada et al 2003). Because we were interested in the possible relationship between circadian rhythm disruptions and hippocampal learning and memory deficits, we used the SAMP8 rather than the SAMP10 for our studies.…”
Section: Senescence-accelerated Mouse As a Model Of Agingmentioning
confidence: 99%
“…In addition, we recently reported that the ingestion of GSE ameliorated cognitive dysfunction and amyloid β (Aβ) accumulation in aged senescence-accelerated mice (SAMP10) [10]. SAMP10 mice exhibit a short life span, brain atrophy in the frontal region, neuronal loss and cognitive dysfunction with aging [11][12][13]. The expression of Ptgds, which encodes lipocalin-type prostaglandin D2 synthase, a putative endogenous Αβ-chaperone, was significantly associated with a green soybean diet [10,14].…”
Section: Introductionmentioning
confidence: 99%